TerraDactyl: A tool for connecting environmental data to when and where - Ariel Levi Simons; Hector Baez; Neha Acharya-Patel; Caren C. Helbing; Jim Jeffers; Julie Stanford; Rachel S. Meyer (Ecological Informatics)
Research ranging from land use planning to ecology benefits from integrating spatial and temporal environmental data. Analyses on multiple environmental datasets are enhanced when there is a common set of variables, improving the ability of researchers to collaborate across a wide variety of projects. Addressing the need, we developed TerraDactyl, an online tool hosted on eDNA Explorer (ednaexplorer.org). TerraDactyl intakes user-provided geospatial coordinates and dates to extract environmental values from a series of datasets hosted on the Google Earth Engine (GEE). We demonstrate the utility of TerraDactyl with two case studies. The first study aims to classify protected areas in the US and Canada given only TerraDactyl data. In the second study we reanalyze published community compositional variation California environmental DNA (eDNA) samples to test whether variation is more strongly associated with environmental factor groups such as soil and topography when more variables are added by TerraDactyl. While some current limitations remain, such as the gaps in data available in polar and coastal regions, TerraDactyl offers a robust integrative tool to assist biodiversity and environmental research that has potential for expansion to include more datasets.